LARANGAN MENIKAH PADA HARI GEBLAK ORANG TUA PERSPEKTIF HUKUM ISLAM: (Studi Kasus Kelurahan Parit Culum II Kecamatan Muara Sabak Barat, Kabupaten Tanjung Jabung Timur Provinsi Jambi - Ishaq, Fadhli Muhaimin; Parwati, Dwi Yuni (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
This article examines the Prohibition of Marriage on the Day of Geblak Parents from the Perspective of Islamic Law in Parit Culum II Village, West Muara Sabak District, East Tanjung Jabung Regency, Jambi Province. The purpose of this research is to find out: 1) the prohibition of marriage on geblak day in Parit Culum Village; 2) The reason for the prohibition of marriage on geblak day; 3) the prohibition of geblak marriage from the perspective of Islamic law. This article uses empirical legal research methods and legal anthropology approaches. The data sources used in this research are; field observations and interviews with several informants related to this issue such as interviews with community leaders, traditional leaders, religious leaders, and village officials of Parit Culum II village while secondary data is obtained through several books related to the theory of marriage and customary law. The data obtained is then analyzed by conducting descriptive data analysis. The result of this research is still the belief in an unfavorable day for conducting a wedding ceremony, which is referred to as the day of the parents' geblak. This tradition has been believed by the people of Parit Culum II Village for generations and is still practiced until now. Second, the provisions of the tradition of the prohibition of marriage on the day of the parents' geblak are not found in a clear or definite text in Islam, even though the practice of this marriage prohibition is not punished as haram.